Synthesis of neutral lipids in chlorella sp. under different light and carbonate conditions - Pérez-Pazos, Jazmín-Vanessa; Fernández-Izquierdo, Pablo (CT&F - Ciencia, Tecnología y Futuro, 2011)
Lipids are biomolecules of great scientific and biotechnological interest due to their extensive applications. Microalgae are potential biological systems used in the synthesis of lipids, particularly Chlorella sp., which is characterized by its high lipid content and for having the right profile for the obtainment of biofuel. Lipid production in microalgae is influenced by several physical and chemical factors. Any modification thereof can cause a stress response represented by changes in synthesized lipid composition, varying from one species to another. This paper evaluates the effect of different light wavelengths, photoperiods and calcium carbonate (CaCO3) supply in lipid synthesis in Chlorella sp. In order to do so, the microalgae was grown in Bold's Basal Medium (BBM) at 20ºC with constant aeration and subject to low blue (470 nm) and red (700 nm) light wavelengths, 0,5 g.L-1 and 1,5 g.L-1 concentrations of CaCO3 and 6-hour light, 18-hour darkness (6:18) and 18-hour light, 6-hour darkness (18:6) photoperiods. The results indicate a higher growth rate for microalgae under red light, 0,5 g.L-1 of CaCO3 and a photoperiod of 6:18. On the other hand, lipid production is higher under blue light, 1,5 g.L-1 of CaCO3 and an18:6 photoperiod. Analysis by gas chromatography indicate that the fatty acids in the samples are oleic, linoleic and palmitoleic, which are of recognized importance in the biodiesel industry. This suggests that neutral lipid synthesis can be optimized in two stages: first, by promoting growth and subsequently, by inducing lipid production.